2009
DOI: 10.2116/analsci.25.211
|View full text |Cite
|
Sign up to set email alerts
|

Peak Parking-Moment Analysis Method for the Measurement of Surface Diffusion Coefficients

Abstract: The peak parking (PP)-moment analysis (MA) method was applied to the measurement of surface diffusion coefficients (Ds) in reversed-phase liquid chromatography using a C18-silica gel and an aqueous solution of methanol (70 vol%). The values of Ds measured by the PP-MA method were in agreement with those obtained by the pulse response (PR)-MA method, which is one of powerful strategies for the quantitative study on the mass transfer kinetics in columns and stationary phases. It was demonstrated that the PP-MA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…It seems that both of them represent the same flux of sample molecules in the stationary phase although they respectively correspond to axial dispersion and intraparticle surface diffusion. In previous papers (27)(28)(29), it has been experimentally demonstrated that D Ls is equal to D s .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It seems that both of them represent the same flux of sample molecules in the stationary phase although they respectively correspond to axial dispersion and intraparticle surface diffusion. In previous papers (27)(28)(29), it has been experimentally demonstrated that D Ls is equal to D s .…”
Section: Discussionmentioning
confidence: 97%
“…A brief explanation about the kinetic data analysis procedure of the PP-MA method is provided in the following. More detailed information can be found in other literature (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak-parking methods have been used previously for the measurement of diffusion coefficients in chromatographic systems [32,35,36,39,40,43,44]. Peak-parking experiments were carried out with the same columns as above and the Acquity UPLC.…”
Section: Methodsmentioning
confidence: 99%
“…Several experimental techniques for determining D S have been proposed [9][10][11][12][13][14][15][16]. For a fixed-bed breakthrough curve, the most common technique used in industrial design is the mass transfer zone (MTZ) method [16][17][18][19] that can be applied to multicomponent systems.…”
Section: Introductionmentioning
confidence: 99%